Combinatorial transient gene expression strategies to enhance terpenoid production in plants - Park, Soyoung; Mani, Vimalraj; Kim, Jin A.; Lee, Soo In; Lee, Kijong (Frontiers in Plant Science, 2022)
The monoterpenoid linalool and sesquiterpenoid costunolide are ubiquitous plant components that have been economically exploited for their respective essential oils and pharmaceutical benefits. In general, monoterpenes and sesquiterpenes are produced by the plastid 2-C-methyl-D-erythritol 4-phosphate (MEP) and cytosolic mevalonate (MVA) pathways, respectively. Herein, we investigated the individual and combinatorial potential of MEP and MVA pathway genes in increasing linalool and costunolide production in Nicotiana benthamiana. First, six genes from the MEP (1-deoxy-D-xylulose-5-phosphate synthase, 1-deoxy-D-xylulose 5-phosphate reductoisomerase, 4-diphosphocytidyl-2-C-methyl-D-erythritol kinase, geranyl pyrophosphate synthase, and linalool synthase) and MVA (acetoacetyl-CoA-thiolase, hydroxy-3-methylglutaryl-CoA reductase, farnesyl pyrophosphate synthase, germacrene A synthase, germacrene A oxidase, and costunolide synthase) pathways were separately cloned into the modular cloning (MoClo) golden gateway cassette. Second, the cassettes were transformed individually or in combination into the leaves of N. benthamiana by agroinfiltration. Five days post infiltration (DPI), all selected genes were transiently 5- to 94-fold overexpressed. Quantification using gas chromatography-Q-orbitrap-mass spectrometry (GC-Q-Orbitrap-MS) determined that the individual and combinatorial expression of MEP genes increased linalool production up to 50–90 ng.mg-1 fresh leaf weight. Likewise, MVA genes increased costunolide production up to 70–90 ng.mg-1 fresh leaf weight. Our findings highlight that the transient expression of MEP and MVA pathway genes (individually or in combination) enhances linalool and costunolide production in plants.